The Effect of Integrated-Neuro-Linguistic Programming as Supplementary Intervention for Individuals with Symptoms of Depression - Ybias, Charito; Ortibano, Mark; Madrigal, Dennis (Technium Social Sciences Journal, 2024)
This study investigated the effectiveness of Integrated Neuro-Linguistic Programming (NLP) as a supplementary intervention for individuals with depressive symptoms in the Philippines. The study employed an A-B Single Case - Multiple-subject Comparative Design with three female participants diagnosed with depression. The intervention, administered by an Internationally Certified Master Practitioner of NLP, utilized various NLP techniques, including the Meta Model, reframing, anchoring, Timeline Therapy®, and hypnotherapy, over four weekly sessions. The Hopkins Symptom Checklist (HSCL) and the Automatic Thoughts Questionnaire (ATQ-30) were used to assess changes in depressive symptoms before and after the intervention. The results showed significant reductions in depressive symptoms across all participants, particularly in areas related to negative self-concept, negative expectations, and low self-esteem. The study highlights the potential of Integrated-NLP as a supplementary intervention for individuals with depression, emphasizing the importance of personalized approaches and further research in this field. The findings contribute to the limited literature on NLP’s clinical application in the Philippines and offer valuable insights for mental health practitioners seeking alternative or complementary interventions for depression.